Neutrophil-to-Lymphocyte and Platelet Ratio (N/LP Ratio), a Reliable Criterion for Predicting In-Hospital Mortality in Both Genders Infected With SARS-CoV-2 - Jafar Mohammadshahi; Hassan Ghobadi; Afshan Shargi; Hossein Moradkhani; Hamed Rezaei; Mahur Kazemy; Mohammad Reza Aslani (Mediators of Inflammation)
Conclusion: A reliable predictor in the current study of men and women with COVID-19 was N/LP ratio.